Energetics, yield, water use and economics of rice (Oryza sativa)-based cropping systems in flood-prone situation of eastern Uttar Pradesh - SINGH, G; MEHTA, R K; SINGH, R V (The Indian Journal of Agricultural Sciences, 2014)
A field experiment was conducted during 1996-99 at Ghaghraghat, Bahraich, Uttar Pradesh, to study the energy requirement, yield, water use and economics of 7 rice (Oryza sativa L.)- based cropping systems in flood-prone arcas. The roce-lentil (Lens culinaris Medikus)-maize (Zea mays L.)+ cowpea (Vigna unguculata (L.) Walp.] (F) system gave significantly hoghest rice-equivalent yield (9.58 tonnes/ha) water-use efficiency (83.83 kg grain/ha-cm), net profit (Rs 30 249/ha), benefit:cost ratio (3.35) and production efficiency (Rs 75.02/day/ha) than rest of the cropping scquences. Rice-wheat (Triticum aestivum L. emend. FioriÂ· & paol.)-maize + cowpea (F) sequence ranked second for net profit (Rs 24 139/ha), rice equivalent (9.19 tonnes/ha), Water use efficiency (61.85 kg grain/ha-cm) and production efficiency (Rs 70.7/day/ha). Rice-pea (Pisum sativum L.s.i.)-maize + cowpea (F) system gave the highest energy input(38.03 MJ x 10 ha), while highest energy output (907.75 MJ x 10/ha) and energy-use efficiency (29.52) were obtained in rice-indian mustard [Brassica juncea (L.) Czernj & Cosson]-maize + cowpea (F) sequence. Land-utilization efficiency was maximum (91.78%) in rice-Iinseed (Linum usitatissimum L.)-maize+ cowpea (F), followed by rice-lentil-maize + cowpea (F) system (90.41 %). Rice-indian mustard-maize + cowpea (F) system gave the lowest net income (Rs: 12 037/ha) and benefit; cost ratio (1.82). Profitability-wise rice-linseed-maize +cowpea (F) and rice-coriander (Coriandrum sativum L.)-maize + cowpea (F) cropping systems were equally good.